2020
DOI: 10.1186/s12961-020-00551-7
|View full text |Cite
|
Sign up to set email alerts
|

Questions for future evidence-informed policy initiatives: insights from the evolution and aspirations of National Immunization Technical Advisory Groups

Abstract: Background: Attention to evidence-informed policy has grown; however, efforts to strengthen the quality and use of evidence are not starting from a blank slate. Changes in health architectures and financing pose different considerations for investments in evidence-informed policy than in the past. We identify major trends that have shifted the environment in which health policies are made, and use the evolution and future aspirations of National Immunization Technical Advisory Groups (NITAGs) in low-and middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…The study established variations in the capacity of TWGs to generate, synthesize and use research evidence, and this means that efforts to build technical capacity should further be strengthened. These results are consistent with ndings of other studies (7)(8)(9)13). Bell (9) further noted that time and publication languages were barriers to use of evidence by decision and policy makers including TWGs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study established variations in the capacity of TWGs to generate, synthesize and use research evidence, and this means that efforts to build technical capacity should further be strengthened. These results are consistent with ndings of other studies (7)(8)(9)13). Bell (9) further noted that time and publication languages were barriers to use of evidence by decision and policy makers including TWGs.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the gap and challenges on the structure and the functionality of TWGs in Malawi and several other countries, there is lack of clarity on how research evidence is utilised in different TWG platforms to inform decisions, and how the TWG discussions are processed and contribute to decision-making at higher levels (9,12,13). This calls for a need to understand the functionality and effectiveness of TWGs in ful lling their de ned mandates, thus the aim of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of national immunization policy by governments is supported by the independent, structured and evidence-informed recommendations and guidance provided by the NITAGs [49]. The issue of allocated budgeting and the part of the Ministry of Finance have been described as highly influential regarding if, when and how NITAG recommendations are adopted and implemented [50]. The NITA Gs worldwide vary as to their affiliation and proximity to the national government, mainly to the Ministry of Health [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“… 15 18 22 A TAG or an SC has been defined as a group of health policy actors/experts who meet on a regular basis to decide on, guide, and evaluate a project's implementation, and to recommend strategies on how to best to achieve the project's goal and objectives. 15 49 Available reports have shown that both TAG and SC have played vital roles in bridging the divide between research and policy and promoting EIPM. Such groups and committees have functioned as health coordination mechanisms and have strengthened the development of a sector-wide approach in facilitating EIPM.…”
Section: Discussionmentioning
confidence: 99%